2021
DOI: 10.1108/joepp-01-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the storm: talent management in internationally oriented Greek small and medium-sized enterprises

Abstract: PurposeBased on a study of internationally oriented Greek small and medium-sized enterprises (SMEs), and using the lens of institutional theory, this paper extends the understanding of the extent to which Greece's institutional context influences talent management (TM). In so doing, the authors focussed on the key TM practices employed by SMEs to enhance and sustain TM: talent acquisition, development and retention. The authors also explore how these practices are shaped by the Greek institutional context.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…It is a key action that transforms people from factors of production into forces of contribution to sustainability; it is a valuable investment and its contribution to a firm's performance has been highlighted. Talent development is a major factor in organizations achieving both organizational and individual desired benefits (Bratton, 2018), and it is a key element of the talent management process that should be dynamic and linked with the strategic trajectory of the organization (Kravariti et al. , 2021).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…It is a key action that transforms people from factors of production into forces of contribution to sustainability; it is a valuable investment and its contribution to a firm's performance has been highlighted. Talent development is a major factor in organizations achieving both organizational and individual desired benefits (Bratton, 2018), and it is a key element of the talent management process that should be dynamic and linked with the strategic trajectory of the organization (Kravariti et al. , 2021).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…The results of this study are also consistent with other conducted studies (Brightman, 2007;Goestjahjanti et Helaly, El-Sayed, 2022). From the same point of view, it has been found that the ability to retain employees in an organization depends on fully developing, understanding and managing their talents (Kravariti et al, 2021). Talent management can therefore be particularly helpful in retaining talented employees and motivating them to stay in the organization, thus reducing staff turnover (Festing, Schäfer, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the presence of powerful owners influences how practices are developed and implemented (Valverde et al , 2013). The power of key decision makers, including CEOs, owners or human resource (HR) managers was also noted in the hospitality industry (Kravariti et al , 2021).…”
Section: Conceptualising Talent Management In Small and Medium-sized ...mentioning
confidence: 99%